Primary School Children’s Vandalism: The Problem of Upbringing and Interaction in Russian Families (European Journal of Mental Health, 2017)
The study is devoted to the problem of primary school children-s vandalism, and particularly its connection with child-parent relationships on the example of Russian families. We define the main predictors of a child-s vandal activity on the basis of psychological diagnostics of 228 8-9-year-old children and the assessment of the frequency and specifics of their vandal behaviour by their 228 parents. The children are classified into 3 groups by the extent of their propensity for vandalism. The complex analysis identifies personal and emotional factors influencing the frequency of a child-s acts of destruction and transformation of other people-s items, devaluation of their own and others- things including those explained by the covert desire to acquire new items. The research findings confirm a significant role of the parent-child relationships in the formation of the child-s readiness for vandal behaviour. In particular, we prove that limitation of a child-s freedom by excessive strictness and hyper protection aggravates children-s propensity for vandalism.